Is the New Media Superior to the Traditional Media for Advertising - Odun, Ogidi; Utulu, Anthony U (Asian Journal of Economic Modelling, 2015)
The advent of new media has had tremendous influence on every aspect of human information dissemination. Consequently, the new media has to a very large extent (re)written histories with impact on some traditional concepts. Adverts are produced to introduce new and reintroduce old products to consumers with the sole aim of persuading them to buy. Broadcast stations also advertise their products for customers (media users) to get abreast of their old and/or new products (programmes), using both traditional and new media platforms. This paper examines the evolution of the new media as an advertising tool and the challenges it poses to the traditional media. With the adoption of non-probability snowball sampling technique to gather the views of users of both traditional and new media, the study observes that while the new media has indeed gained much acceptance and patronage globally because of its convergence, reduced organizational expenses and time/space saving; it is still an extension of the traditional and not a replacement for it. This observation is of utmost importance when one realizes that while demand for the use of the new media has expanded considerably world-wide, its use in the developing countries has been circumscribed by low Internet connectivity, disrupted power supply, damaged digital equipment maintenance, and low income to access the new media in these countries. If the information needs of the world’s largest population, that is, the people in the rural areas of developing countries are to be met, there is still the need for traditional and new media to co-exist for some time to come. Both media should work together and make use of each other’s comparative advantage to confront unfolding events in the global business environment.